Negotiating the Identity of Punk Children, Descriptive Study of the Phenomenon of Punk Children : Negosiasi Identitas Anak Punk, Studi Deskriptif Fenomena Anak Punk - Erwinsyah, Derry; Sinduwiatmo, Kukuh (Universitas Muhammadiyah Sidoarjo, 2023)
Punk has been known to the public as a social group that has different characteristics from other communities, the lifestyle of punk children is the result of western culture which is accepted and applied in the social life of teenagers. At the beginning of the formation of the punk community, the principle was that without a leader in the community (no seniority), they prioritized solidarity, togetherness and kinship. The punk community is formed due to a factor or a problem from the family or other factors from each individual. In Singosari there are many punk children who live and settle there from outside the city or from Malang itself. This study aims to describe the identity negotiation of punk children in Singosari Malang. The method used in this research is qualitative. The population of this research is the Punk Community. Purposive Sampling technique for sampling while data collection using observation, interviews and documentation. The data analysis technique uses data reduction, data presentation and conclusion drawing. The results of this study are the identity of punk children in Singosari Malang is formed from interpersonal communication that has been carried out in their daily lives both with the punk community and with the community, the existence of openness, equality, empathy, support and positive attitudes carried out by punk children in mingling with the community so that its existence is well received.